DIFFERENCES IN PSYCHOLOGICAL ADAPTATION, PREDICTORS AND FEATURES OF PSYCHOLOGICAL AND SOCIAL MALADJUSTMENT FORMATION IN FOREIGN STUDENTS OF MEDICAL INSTITUTIONS OF HIGHER EDUCATION IN UKRAINE - Borysenko, V.V.; Herasymenko, L.O.; Isakov, R.I.; Fysun, Yu.O.; Kydon, P.V.; Shynder, V.V.; Kazakov, O.A. (World of Medicine and Biology, 2023)
The psychological adaptation of international students to a Ukrainian higher medical school depends on individual and group factors, motivational and background characteristics, cognitive, information-cognitive and gnostic factors, interpersonal relations in international study groups, and the formation of psychosocial maladaptation in foreign students indicates the need to create forms and methods of a differentiated approach to the personality of each student. The study describes the psychological differences in adaptive mechanisms among international students, the presence and severity of psychosocial maladjustment in various areas, and the factors shaping its development. It is shown that the education of international students in medical higher education institutions contributes to integrating domestic medical schools into the global intellectual space and, therefore, stimulates the development of medical science and practice in the country.